2021
DOI: 10.3102/00346543211046984
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Video Coaching, From Design Features to Student Impacts: A Systematic Literature Review

Abstract: Video and coaching as vehicles for teachers’ professional development have both received much attention in educational research. The combination of the two, video coaching, where teachers watch and discuss videos of their own practice with a coach, seems especially promising, but there is limited insight into how the design leads to desired teacher and student outcomes through mediating enactment processes. This review systematically synthesized the occurrences and co-occurrences of video coaching design featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 105 publications
2
10
0
1
Order By: Relevance
“…Last but not least, the finding that the video group also improved in triggered interest and self-efficacy in classroom management, although to a lesser extent, speaks to the longacknowledged benefits of classroom recordings (eg, Tripp & Rich, 2012;van der Linden et al, 2022). Our findings also confirmed that the video task imposed less extraneous cognitive load than VR.…”
Section: Potential Risk Of Vr and Its Remediessupporting
confidence: 72%
See 1 more Smart Citation
“…Last but not least, the finding that the video group also improved in triggered interest and self-efficacy in classroom management, although to a lesser extent, speaks to the longacknowledged benefits of classroom recordings (eg, Tripp & Rich, 2012;van der Linden et al, 2022). Our findings also confirmed that the video task imposed less extraneous cognitive load than VR.…”
Section: Potential Risk Of Vr and Its Remediessupporting
confidence: 72%
“…Classroom video has long been incorporated into different stages of teacher education (Santagata et al, 2021;van der Linden et al, 2022). In the pre-service stage, video is considered an advantageous medium (Ramos et al, 2021) that helps student teachers "to activate, acquire, and apply knowledge in a meaningful way" (Blomberg et al, 2013, p. 93).…”
Section: Video As a Popular Training Medium For Classroom Managementmentioning
confidence: 99%
“…In recent decades, the use of video in teacher professional learning has increased (Seago, 2003). The use of video-based teaching in teacher preparation has become a significant element of teacher education programs and has shown the most significant benefits in motivation, optimized cognition, and improved classroom practices (Gaudin & Chaliès, 2015;Hamel & Viau-Guay, 2019;Hrastinski, 2021;Ramos et al, 2021;van der Linden et al, 2022). Video allows teachers to focus on students' ideas, instructional interactions, or teaching actions.…”
Section: Video As a Tool For Analyzing Student Thinking In Teacher No...mentioning
confidence: 99%
“…Video provides the opportunity for collaborative review and consensus coding, training and building inter-rater reliability as well as coaching skills to support each teacher and the children in their classroom (van der Linden et al, 2022). Video enables fast-cycle trials to evaluate the impact of professional development and individualized coaching, supporting innovation within the coaching staff, and leverages the potential to get rapid feedback from a video within a short period of time to observe if there is an improvement in teachers' application of teaching practices and fidelity of implementation.…”
Section: Learning and Research Benefitsmentioning
confidence: 99%
“…Video enables fast-cycle trials to evaluate the impact of professional development and individualized coaching, supporting innovation within the coaching staff, and leverages the potential to get rapid feedback from a video within a short period of time to observe if there is an improvement in teachers' application of teaching practices and fidelity of implementation. Moreover, video data can be re-analyzed in the future as fidelity measures are revised, providing an on-going source of valuable data (e.g., Clarke and Hollingsworth, 2002;van der Linden et al, 2022).…”
Section: Learning and Research Benefitsmentioning
confidence: 99%